Pengaruh Penyuluhan Kesehatan Tentang Deteksi Dini Ca Serviks Terhadap Motivasi Wanita Usia Subur Melakukan Pemeriksaan IVA Di Wilayah Kerja Puskesmas - Erlina Bahar (Jurnal Rumpun Ilmu Kesehatan, 2021)
The purpose of this study was to determine the effect of health education on early detection of cervical cancer on the motivation of women of childbearing age to carry out VIA examinations in the working area of ​​the Antang Health Center in 2021. This type of research was an analytical survey method with a cross sectional study approach. With a population of 197 people and a sample of 30 people, the sampling technique used was purposive sampling. Data analysis was performed by Mc.Nemar test. The results of statistical tests on all respondents using the Mc.Nemar test obtained p value of 0.000 < p value of 0.05. HO is rejected It has been accepted, then there is an influence on women of childbearing age carrying out an IVA examination in the Antang Health Center Work Area in 2021.